2023
DOI: 10.3389/fsurg.2022.1046713
|View full text |Cite
|
Sign up to set email alerts
|

New insights into a microvascular invasion prediction model in hepatocellular carcinoma: A retrospective study from the SEER database and China

Abstract: Background and AimsThe prognosis of liver cancer is strongly influenced by microvascular infiltration (MVI). Accurate preoperative MVI prediction can aid clinicians in the selection of suitable treatment options. In this study, we constructed a novel, reliable, and adaptable nomogram for predicting MVI.MethodsUsing the Surveillance, Epidemiology, and End Results (SEER) database, we extracted the clinical data of 1,063 patients diagnosed with hepatocellular carcinoma (HCC) and divided it into either a training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Studies 24,25 have shown that the size of the tumor is a significant risk factor for the emergence of MVI and postoperative recurrence of HCC. The incidence of MVI and postoperative recurrence in HCC patients increases progressively with increasing tumor diameter 26 . Tumor size was separated into three groups in this study, with cutoff values of 20 and 50 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies 24,25 have shown that the size of the tumor is a significant risk factor for the emergence of MVI and postoperative recurrence of HCC. The incidence of MVI and postoperative recurrence in HCC patients increases progressively with increasing tumor diameter 26 . Tumor size was separated into three groups in this study, with cutoff values of 20 and 50 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that the maximal diameters of MVI-positive HCCs were significantly larger than those of MVI-negative HCC, and a larger maximal diameter was an independent risk factor for MVI-positive HCCs with an odds ratio of 1.021. Tumor size is an established independent prognostic factor for HCC[ 20 , 21 ]. Our research has revealed that HCC size was also an independent prognostic factor for positive MVI.…”
Section: Discussionmentioning
confidence: 99%